The relationship between state-fear of missing out, loneliness, adaptive perfectionism and social media use in university students: a questionnaire and intervention study - Jin Wan; Zishu Zhou (BMC Psychology)
Abstract Background State-Fear of Missing Out (State-FoMO) has been rising in prevalence among Chinese university students. This study explores the relationships between university students’ State-FoMO, loneliness, and social media use, as well as the moderating role of adaptive perfectionism. Methods Questionnaire data were collected from 1075 university students. Hierarchical regression analyses (via SPSS) were conducted to test direct effects, and the bootstrap method (via PROCESS) was used to examine the mediating role of social media use and the moderating role of adaptive perfectionism. An intervention experiment was conducted with a control group design, comprising 40 participants in each of the two experimental groups (receiving a 14-day intervention combining seven sessions of group psychological counseling—focused on trust-building, self-exploration, emotional regulation, and social skills—and daily 15-minute ICBT components) and 40 in the control group. Results (1) Loneliness can lead to social media use (β = 0.30, p < 0.001). (2) Social media use has a significant positive effect on State-FoMO (β = 0.46, p < 0.001). (3) Social media use partially mediated the relationship between loneliness and State-FoMO. (4) Adaptive perfectionism negatively moderated the relationship between loneliness and social media use (β=-0.11, p < 0.001). (5) Adaptive perfectionism plays a negative moderating role in the path of “loneliness, social media use, and State-FoMO.” (6) Group psychological intervention can effectively reduce students’ loneliness, thereby alleviating their social media use and State-FoMO. Conclusion Lonely university students often turn to social media for emotional support, which can lead to State-FoMO. However, adaptive perfectionism can lessen the effect of loneliness on social media use and State-FoMO. ICBT-based group counseling can reduce loneliness and, consequently, social media use and State-FoMO among university students.